2020
DOI: 10.1002/app.49354
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on two modification strategies for the reinforcement of biodegradable lignin/poly(lactic acid) blends

Abstract: In this work, biodegradable lignin/poly(lactic acid) (PLA) blends were prepared with melting compounding method. Dicumyl peroxide (DCP) and maleic anhydride (MA)/biphenyl peroxide (BPO) were used for the modification of the polymer blends, respectively. Structure of the polymer blends was characterized with Fourier transformed infrared spectroscopy and field emission scanning electron microscopy. Mechanical properties of the samples were determined with universal test machine and dynamic mechanical analysis. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Downstream of the thermogravimetric experiments they speculated about the activation of PLA degradation by the abundant hydroxyl groups of the lignin, through thermohydrolysis and β-scission, which led to the lower molecular weight of PLA and the poorer thermal stability of the modified blends. In conclusion they observed a general increase of the mechanical strength but not an improvement in thermal stability and a lowering of glass transition temperature and melting temperature compared to pure PLA [ 43 ].…”
Section: Thermal Techniques In Polymers’ Bio-reinforcementmentioning
confidence: 99%
“…Downstream of the thermogravimetric experiments they speculated about the activation of PLA degradation by the abundant hydroxyl groups of the lignin, through thermohydrolysis and β-scission, which led to the lower molecular weight of PLA and the poorer thermal stability of the modified blends. In conclusion they observed a general increase of the mechanical strength but not an improvement in thermal stability and a lowering of glass transition temperature and melting temperature compared to pure PLA [ 43 ].…”
Section: Thermal Techniques In Polymers’ Bio-reinforcementmentioning
confidence: 99%
“…Liu et al investigated the effect of MAH- g -PBS compatibilizer on lignin/PBS composites, and they found that the addition of compatibilizer enhanced the mechanical properties of composites, especially tensile and flexural strength . In the work of Ge et al, MAH- g -PLA was successfully used in PLA/lignin composites, and the interfacial connection of lignin and PLA was improved through grafting reaction . The results showed that the tensile strength increased from 59.9 to 71.6 MPa and elongation at break rose from 3.8% to 5.0%.…”
Section: Plasticizer Compatibilization Between Bpps and Ligninmentioning
confidence: 99%
“…The widespread consumption of conventional plastics has brought about serious environmental concerns, among them being that nondegradable waste plastics now threaten the health of humanity 1 . There is an emerging trend to increase the use of bio‐based polymers as a replacement for persistent fossil‐based polymers 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Polylactic acid (PLA), a thermoplastic polymer made by ring‐opening polymerization of lactide or condensation of lactic acid monomers is an important sustainable polymer material 1 . However, its high production cost and some undesirable properties, including brittleness, poor heat resistance, limited gas barrier properties, and poor UV barrier properties, can limit its application.…”
Section: Introductionmentioning
confidence: 99%